2014
DOI: 10.3233/jpd-130320
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of Rotigotine Dose Response on ‘Off’ Time in Advanced Parkinson's Disease

Abstract: Background: Previous phase III studies in patients with advanced Parkinson's disease (PD) not adequately controlled on levodopa demonstrated significant reduction of 'off' time with rotigotine transdermal system up to 16 mg/24 h. However, the minimal effective dose has not been established. Objective: This international, randomized, double-blind, placebo-controlled study (SP921; NCT00522379) investigated rotigotine dose response up to 8 mg/24 h. Methods: Patients with advanced idiopathic PD (≥2.5 h of daily 'o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 18 publications
0
45
0
Order By: Relevance
“…16 The efficacy of rotigotine in improving UPDRS II and III subscores has been consistently shown in large-scale studies in advanced-stage PD. [25][26][27] Thus, the relatively small numerical improvement in the UPDRS II + III total score (exploratory P value >.05) in the current study was likely due to patients being included based on the severity of their PD-associated pain rather than the severity of motor symptoms (which were reasonably well controlled in this patient population) and the activities of daily living symptoms. Rotigotine was generally well tolerated in a dose range of 4 to 16 mg/24 h, with few patients discontinuing the study as a result of AEs, and AEs were consistent with the known safety profile of rotigotine.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…16 The efficacy of rotigotine in improving UPDRS II and III subscores has been consistently shown in large-scale studies in advanced-stage PD. [25][26][27] Thus, the relatively small numerical improvement in the UPDRS II + III total score (exploratory P value >.05) in the current study was likely due to patients being included based on the severity of their PD-associated pain rather than the severity of motor symptoms (which were reasonably well controlled in this patient population) and the activities of daily living symptoms. Rotigotine was generally well tolerated in a dose range of 4 to 16 mg/24 h, with few patients discontinuing the study as a result of AEs, and AEs were consistent with the known safety profile of rotigotine.…”
Section: Discussionmentioning
confidence: 80%
“…These results suggest that rotigotine treatment may potentially be beneficial for the treatment of fluctuation-related pain. Previous studies have demonstrated improvements in wearing-off-type motor fluctuations with rotigotine in patients with advancedstage PD inadequately controlled on levodopa, [25][26][27] and clinical experience suggests that dopaminergic therapy may provide benefits for those nonmotor symptoms that are motor fluctuation-related (ie, wearing-off symptoms such as off-period pain). 15,39 It is worth noting that an approximate 4-fold numerical difference in favor of placebo was observed in KPPS domain of "chronic pain"; however, baseline "chronic pain" scores were 2-fold higher in the placebo group than in the rotigotine group; thus, these results are difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotigotine has repeatedly been shown to improve ADL and motor function as measured on the UPDRS part II and/or III in patients with either early or advanced PD when compared to the placebo control group 12,[27][28][29][30][31][32][33][34][35][36] Rotigotine also reduces "off" time significantly as an add-on to L-dopa in patients with mid-to advanced-stage PD. 29,34,35,37 One study showed that rotigotine doses ≤8 mg/24 hr did not reach noninferiority to ropinirole doses ≤24 mg/24 hr, but were instead similar to the efficacy of ropinirole doses ≤12 mg/24 hr. 33 This was supported by a study that showed that ≤16 mg/24 hr rotigotine was noninferior to ≤15 mg/24 hr ropinirole in its effect on UPDRS II and III and on changes in "on" and "off" duration.…”
Section: Rotigotine Motor Symptomsmentioning
confidence: 99%
“…34 Some studies suggested an increased occurrence of dyskinesias in patients with rotigotine compared to placebo controls. 29,34,37 The studies mainly focus on the use of rotigotine as a monotherapy in early PD and as an add-on in mid-stage to advanced PD. However, when rotigotine monotherapy no longer has the desired effect, the clinical practice is often to use rotigotine simultaneously with L-dopa also at a relatively early stage of PD.…”
Section: Rotigotine Motor Symptomsmentioning
confidence: 99%